2007
DOI: 10.1111/j.1365-2044.2006.04899.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetists' management of oxygen pipeline failure: room for improvement*

Abstract: SummaryOxygen pipeline failure is a rare but potentially catastrophic event which can affect the care of patients throughout an entire hospital. Anaesthetists play a critical role in maintaining patient safety, and should be prepared to support an institution-wide emergency response if oxygen failure occurs. We tested the preparedness for this through observation of 20 specialist anaesthetists to a standardised simulator scenario of central oxygen supply failure. Responses were documented using multiple approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 18 publications
0
21
0
2
Order By: Relevance
“…Participants all made errors, (although some participants made only a few), but they made different ones. Only one error (failure to disconnect the wall supply and failure to test it before using it again in the oxygen failure scenario) was made by all participants; this has been discussed in detail elsewhere [43]. The fact that many participants successfully avoided most of the errors suggests that few individual aspects of the simulations were unreasonably challenging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants all made errors, (although some participants made only a few), but they made different ones. Only one error (failure to disconnect the wall supply and failure to test it before using it again in the oxygen failure scenario) was made by all participants; this has been discussed in detail elsewhere [43]. The fact that many participants successfully avoided most of the errors suggests that few individual aspects of the simulations were unreasonably challenging.…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies have demonstrated the promise of simulation in anaesthesia research [26,28,33,43]. We have added to this work by describing a generic research design for the simulation-based evaluation of interventions to improve safety in anaesthesia, and demonstrating that it has sufficient power to be used in studies of reasonable size.…”
Section: Discussionmentioning
confidence: 99%
“…Weller (2007) 9 published an article where it states that oxygen pipeline failure is a rare, but potentially catastrophic event, which can affect the care of patients throughout the hospital.…”
Section: I) Competency Of Anaesthesiologists To Manage Central Oxygenmentioning
confidence: 99%
“…Technical failure in gas supply is so rare it may be as unthinkable as water in the fuel tank of a car. In a simulator scenario in New Zealand, all 20 anaesthetists studied were able to cope safely with a central oxygen supply failure due to total loss of gas pressure [20]. Nevertheless, 'no anaesthetist disconnected the wall pipeline supply, and all subsequently used the reconnected oxygen pipeline supply without testing, with the potential to deliver contaminated gases to the patient' [20], demonstrating the anaesthetist's trust in the gases delivered by central gas supply.…”
Section: ó 2007 the Authorsmentioning
confidence: 99%